Immersive virtual reality reminiscence activities: assessment of engagement and participation, behavioral and psychological symptoms and weel-being of people with dementia - Pereira, Miguel Araújo (2024)
Virtual reality (VR) is a novel technology tha can be used to promote reminiscence among people with dementia, and there are still few studies on the contribution of the immersiveness allowed by VR to enhance therapeutic results. The aim of this study was to analyze the effect of na immersive VR reminiscence session compared to a non-immersive reminiscence session, interms of engagement and participation, behavioral and psychological symptoms and well-being in people with dementia, using behavioral observation and measurement of psychological metrics during interventions. A randomized crossover trial was carried out, with a washout duration of seven days. 20 participants with dementia were recruited, with an average age of 80.55 years and of which 18 (90%) were women. The results indicated that there were significant differences in higher behavioral engagement (Z=-2.67, P=.008), higher apathy during the session, in terms of facial expressions (z=-2.12, P=.034) and lower apathy during the session, in terms of purposeful activity (z=-2.24, P=.025) in the immersive intervention compared to the non-immersive intervention. Moreover, the results indicated that the mean heart rate in the baseline rest condition was significantly lower tahn in the exposure condition, despite the type of intervention (F (1.235,19.764) = 4.333, P= .043). The results suggest that the immersiveness promoted by VR can be useful in promoting engagement of people with dementia in intervention programs. As these technologies are increasingly accessible and safe, it is justified to continue studying their contribution to enhancing therapeutic results.